Goodbye to serve and volley style of play: or do we need to change sport performance priorities? - Durovic, N.; Hraste, M.; Stanišic, L. (Journal of Physical Education and Sport, 2021)
Problem elaboration: Whereas the official game statistics represent the player's partial performance, the overall performance quality contains all factors of overall quality evaluated by experts. Therefore, it is essential to determine their opinion on the significance of coefficients for all the criteria which are defined with respect to a particular playing style in tennis. Intended purpose: The aim of this study was to establish and explain offence and defence priorities for elite serve-volley players. Approach: On the basis of expertise of seven tennis experts,this paper aims to determine the relative importance coefficients regarding serve-volley style of play for eighteen overall performance evaluation criteria. From each given matrix, importance coefficient vectors defined by each of the experts were calculated by means of the Geometric Mean Method and used to form an importance coefficient matrix for a serve-volley player. For this purpose, the vectors of arithmetic means and standard deviations were computed from the procured indices.Findings: The top of the offence hierarchical structure indicates that the first serve quality and the second serve quality have very high importance (AM 0.192; AM 0.166), whereas the net shots quality has high importance (AM 0.146). In addition, the top of the defence hierarchical structure indicates that the second serve return quality has very high importance (AM 0.229), the first serve return quality has high importance (AM 0.178), whereas the defence backhand quality has medium to high importance (AM 0.145). Conclusion: The study has defined defence and offence priorities for the serve-volley style of play. The findings of this study can be implemented by coaches in their selection of suitable tactical solutions and the optimization of the training process among elite tennis players.